2015
DOI: 10.5430/afr.v4n4p1
|View full text |Cite
|
Sign up to set email alerts
|

The Long-run Performance of Chinese Private Firm IPOs

Abstract: This paper examines the three-year long run performance of Initial Public Offerings (IPOs) in the Chinese stock markets from 2002 to 2012. We find that private firm IPO long-term returns are significantly higher than those of non-private firms, measured by both cumulative abnormal returns (CARs) and buy-and-hold abnormal returns (BHARs). Furthermore, the long-term performance of IPOs in the Chinese stock markets seems to have a significant upward tendency after the Non-tradable share (NTS) reform launched in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Supporting the theories, Durukan (2002) and Giovannini (2010) reported a positive relationship between debt-equity ratio and long-run performance of SME IPOs. On the contrary, Liu et al (2012) and Chi et al (2015) reported a negative relationship between the two on the pretext of their vulnerability to financial distress. Based on the above findings, the study hypothesizes that:…”
Section: Hypotheses Developmentmentioning
confidence: 89%
See 3 more Smart Citations
“…Supporting the theories, Durukan (2002) and Giovannini (2010) reported a positive relationship between debt-equity ratio and long-run performance of SME IPOs. On the contrary, Liu et al (2012) and Chi et al (2015) reported a negative relationship between the two on the pretext of their vulnerability to financial distress. Based on the above findings, the study hypothesizes that:…”
Section: Hypotheses Developmentmentioning
confidence: 89%
“…The positive relation of underpricing with long-run returns though contradicts market overreaction/fad hypothesis stands in consonance with the theorists who theorize that firms use underpricing as a signaling device to communicate firm’s true value to investors (Allen and Faulhaber, 1989; Welch, 1989). As underpricing is a cost to the issuing firm, Levis (1993) and Chi et al (2015) argues that only the firms with good quality can bear the cost of underpricing and this good quality translates into investor positive sentiment in issue, leading to higher long-run returns. All models of Table 4 and Models 2, 3 and 4 of the table 5 reflect these findings.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations